2019
DOI: 10.3390/rs11030295
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the Geostationary Ocean Color Imager (GOCI) Remote Sensing Reflectance for Assessing Diurnal Variability of Biogeochemical Processes

Abstract: Short-term (sub-diurnal) biological and biogeochemical processes cannot be fully captured by the current suite of polar-orbiting satellite ocean color sensors, as their temporal resolution is limited to potentially one clear image per day. Geostationary sensors, such as the Geostationary Ocean Color Imager (GOCI) from the Republic of Korea, allow the study of these short-term processes because their orbit permit the collection of multiple images throughout each day for any area within the sensor’s field of reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
(56 reference statements)
2
19
0
Order By: Relevance
“…Such results appear inconsistent with the conventional understanding of the physical and biogeochemical characteristics of the open ocean, where changes in water constituents and the associated optical properties are considered negligible over the course of a day. For example, water columns in an open ocean region were assumed to be diurnally invariant by Concha, Mannino, Franz and Kim [ 25 ], and they used this assumption to gauge the uncertainties in GOCI ocean color products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results appear inconsistent with the conventional understanding of the physical and biogeochemical characteristics of the open ocean, where changes in water constituents and the associated optical properties are considered negligible over the course of a day. For example, water columns in an open ocean region were assumed to be diurnally invariant by Concha, Mannino, Franz and Kim [ 25 ], and they used this assumption to gauge the uncertainties in GOCI ocean color products.…”
Section: Resultsmentioning
confidence: 99%
“…Real geostationary measurements from GOCI have been used to demonstrate its advantages over coastal oceans by tracking the diurnal changes in the sediment plumes of riverine estuaries [ 6 , 22 ], documenting the short-term spatial and vertical redistributions of harmful algal blooms [ 5 , 7 , 23 ], and detecting the continuous evolution of internal waves [ 24 ], etc. In the open ocean, however, the optical characteristics of the water column have commonly been considered diurnally invariant; this assumption has even been applied to determine the accuracy of the GOCI ocean color products [ 25 ]. In contrast, previous in situ investigations have demonstrated that the concentrations of water constituents and their optical properties vary considerably over a short period (daily or hourly) in clear oceanic waters [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…GOCI is the first geostationary ocean color satellite sensor, onboard the South Korean Communication, Ocean and Meteorological Satellite (COMS). It has successfully collected data covering geographical regions between 110 • E and 150 • E, and 2 • N and 50 • N, with a 500-m spatial resolution, since its launch in June 2010 [16,32]. GOCI was designed to measure six visible light bands (at 412, 443, 490, 555, 660 and 680 nm) and two near infrared bands (at 745 and 865 nm) with hourly observations during the daytime.…”
Section: Study Areas and Goci Datamentioning
confidence: 99%
“…In most conditions, valid samplings are often limited: routine field surveys are generally conducted monthly by local authorities, such as the environmental or water quality agency. The most widely used Terra/Aqua MODIS satellites, designed to perform two observations a day, are particularly prone to disruption from cloud coverage and other poor weather conditions, as well as sun glints [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation